Treatment method of lithium iron phosphate and application of lithium iron phosphate in low-temperature lithium ion battery
By stirring and leaching, lithium iron phosphate material is constructed to solve the problem of the degradation of lithium iron phosphate positive electrode material at low temperatures, and a significant improvement in the low-temperature performance of the battery and a process suitable for industrial production is achieved.
Patent Information
- Application Number
- CN202411741888.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
AI Technical Summary
The specific capacity of the existing lithium iron phosphate cathode materials has severely decreased under low temperature conditions, and the capacity retention rate has been significantly reduced, making it difficult to take into account the demand for low temperature performance and industrial production.
By mixing lithium iron phosphate with water, stirring and leaching for more than 0.5 hours, solid-liquid separation is performed to prepare lithium iron phosphate material, build lithium vacancies, and increase the lithium ion diffusion coefficient, thereby improving the low-temperature kinetic performance.
This method is simple and suitable for commercially available conventional lithium iron phosphate raw materials. The resulting material has excellent performance and significantly improves the low-temperature performance of the battery and the capacity retention rate of different magnifications at room temperature.
Smart Images

Figure CN119551648A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium ion battery positive electrode materials, and specifically relates to a lithium iron phosphate processing method and an application thereof in low-temperature lithium ion batteries. Background Art
[0002] Among the common lithium-ion battery materials currently used, lithium iron phosphate cathode materials are widely used due to their stable charge and discharge platform, long cycle life, high safety and low cost. However, compared with other cathode materials, low temperature will cause a serious decrease in the specific capacity of lithium iron phosphate batteries (lithium-ion batteries using lithium iron phosphate as cathode material) and a significant decrease in capacity retention. The temperature in northern my country often reaches below 0°C in winter, and some special equipment is even in a low-temperature working environment below -40°C for a long time. It is very important to give full play to the characteristics of lithium iron phosphate cathode materials and further improve their low-temperature performance to broaden the application scenarios of lithium iron phosphate batteries.
[0003] The Chinese invention patent application with the application publication date of November 20, 2013 and the application publication number of CN103400964A discloses a method for preparing a lithium iron phosphate electrode, which is to disperse nano-scale lithium iron phosphate particles in an organic solvent, and then perform secondary granulation by spray granulation to obtain lithium iron phosphate secondary particles with a median particle size of 4 to 5 μm; then use an adhesive (such as polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber, etc.) and lithium iron phosphate secondary particles to stir on a dry mixing device for 0.1 to 3 hours, and then disperse with a dispersant, two or more conductive agents and solvents such as N-methylpyrrolidone by ultrasonic dispersion to obtain an electrode slurry. The lithium iron phosphate electrode prepared based on the electrode slurry can improve the rate performance and low-temperature discharge performance of the battery.
[0004] The reason why the above lithium iron phosphate electrode can improve the low-temperature discharge performance of the battery is that the 4~5μm lithium iron phosphate secondary particles are composed of a large number of primary nanoparticles, with a large number of interconnected channels inside, which can provide channels for the ion transmission of the electrolyte. The lithium iron phosphate electrode requires the use of extremely expensive nano-scale lithium iron phosphate particles, and the preparation requires the use of organic solvents for secondary granulation. In addition, the secondary particles need to be mixed with a binder in advance before they can be used for pulping. The overall raw material and production costs are high, the process is complicated, and it is not suitable for large-scale promotion and application. Summary of the invention
[0005] The purpose of the present invention is to provide a method for processing lithium iron phosphate to solve the problem that the existing lithium iron phosphate material is difficult to achieve both low temperature performance and suitability for industrial production.
[0006] The second object of the present invention is to provide the application of the lithium iron phosphate material obtained by the above-mentioned treatment method in low-temperature lithium-ion batteries.
[0007] In order to achieve the above first purpose, the technical solution adopted by the present invention is: A method for treating lithium iron phosphate comprises the following steps: mixing lithium iron phosphate and water, stirring and leaching for more than 0.5h, and then performing solid-liquid separation to obtain lithium iron phosphate material.
[0008] The present invention is a pioneering invention. Different from the prior art method of constructing secondary particles, the present invention uses stirring leaching to remove residual lithium near the surface of lithium iron phosphate particles and internal lattice lithium from the positive electrode material, construct lithium vacancies inside the material, increase the lithium ion diffusion coefficient, and thus improve the low-temperature kinetics of lithium iron phosphate positive electrode materials. The treatment method has the characteristics of simple process and convenient operation. It is suitable for all kinds of commercially available conventional lithium iron phosphate raw materials and is suitable for industrial production; the obtained lithium iron phosphate material has excellent performance, can effectively improve the low-temperature performance of the battery, and has stable product quality. In addition, the capacity retention rate of the lithium iron phosphate material prepared by this treatment method at different rates at room temperature can also be significantly improved, proving the effectiveness of this method in improving material kinetics.
[0009] Preferably, the stirring leaching time is 0.5 to 24 hours. Further preferably, the stirring leaching time is 6 to 24 hours. More preferably, the stirring leaching time is 8 to 24 hours.
[0010] Preferably, the stirring speed of the stirring leaching is 200-1000 rpm. Further preferably, the stirring speed of the stirring leaching is 600-1000 rpm.
[0011] Preferably, the mixing mass ratio of the lithium iron phosphate to water is 1:100-150.
[0012] Preferably, the solid obtained after the solid-liquid separation is washed and vacuum dried to obtain the lithium iron phosphate material; the temperature of the vacuum drying is 100-150°C.
[0013] In order to achieve the above second purpose, the technical solution adopted by the present invention is: The lithium iron phosphate material obtained by the above treatment method is used in low-temperature lithium-ion batteries.
[0014] The low-temperature lithium-ion battery using the above-mentioned lithium iron phosphate material artificially constructs lithium vacancies in the lithium iron phosphate positive electrode, which has been experimentally confirmed to be beneficial to improving the low-temperature energy storage and conversion of the battery. It has significantly improved low-temperature discharge performance, thereby optimizing the low-temperature application of lithium iron phosphate batteries.
[0015] Preferably, the low-temperature lithium-ion battery has a 0.1C discharge capacity retention rate of more than 65% at -40°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is a comparison chart of -40°C discharge capacity retention rate of various embodiments and comparative examples in the experimental examples of the present invention. DETAILED DESCRIPTION
[0017] The lithium ion diffusion coefficient of lithium iron phosphate is very low, resulting in poor low-temperature performance of lithium-ion batteries. The technical concept of the present invention is to remove the residual lithium near the surface of lithium iron phosphate particles and the internal lattice lithium from the positive electrode material by water washing, and construct lithium vacancies inside the material, so that whether it is the process of lithium removal or lithium insertion, it can reduce the potential barrier, improve its low-temperature kinetic characteristics, increase the lithium ion diffusion coefficient, and thus improve its low-temperature performance. At the same time, the capacity retention rate of the material at different rates at room temperature can also be significantly improved.
[0018] The conditions of water washing (i.e. stirring leaching) will affect the formation of lithium vacancies. Controlling the stirring leaching speed to 200~1000rpm and the time to 0.5~24h can achieve a good treatment effect. The longer the water washing time and the higher the speed, the more lithium vacancies are generated. When the speed reaches above 600rpm and the time reaches above 6h, the low-temperature discharge performance of the battery can be significantly improved. During water washing, the mixing mass ratio of lithium iron phosphate raw material and water can be controlled to 1:100~150. The temperature of stirring leaching can be controlled at 25±2℃.
[0019] After stirring and leaching, the solid and liquid are separated, and then washed twice with 5-20 times deionized water (25±2℃), and then vacuum dried at 100~150℃ to complete the treatment of lithium iron phosphate.
[0020] The implementation process of the present invention is described in detail below in conjunction with specific embodiments. In the following embodiments and comparative examples, the particle size of the lithium iron phosphate powder material is 0.3-35 μm.
[0021] 1. Specific embodiment of the method for treating lithium iron phosphate of the present invention Example 1 The method for processing lithium iron phosphate of this embodiment includes the following steps: (1) Take 500 mL of deionized water and slowly add 5 g of lithium iron phosphate powder to it and stir to form a uniform suspension.
[0022] (2) Stir continuously for 0.5 h at 200 rpm, then filter the solution to remove the lithium iron phosphate material, and then wash twice with 80 mL of deionized water.
[0023] All the above operating environment temperatures and solution temperatures are 25° C. The washed lithium iron phosphate material is dried under vacuum conditions at 120° C. to constant weight (complete drying) to obtain the final product.
[0024] Example 2 The method for processing lithium iron phosphate of this embodiment includes the following steps: (1) Take 500 mL of deionized water and slowly add 5 g of lithium iron phosphate powder to it and stir to form a uniform suspension.
[0025] (2) Stir continuously for 0.5 h at 400 rpm, then filter the solution to remove the lithium iron phosphate material, and then wash twice with 80 mL of deionized water.
[0026] All the above operating environment temperatures and solution temperatures are 25° C. The washed lithium iron phosphate material is dried under vacuum conditions at 120° C. to constant weight (complete drying) to obtain the final product.
[0027] Embodiment 3-5 The lithium iron phosphate treatment methods of Examples 3-5 are different from those of Example 2 only in rotation speed, and other conditions are the same. In the lithium iron phosphate treatment methods of Examples 3, 4, and 5, the rotation speeds are 600 rpm, 800 rpm, and 1000 rpm, respectively.
[0028] Example 6 The method for processing lithium iron phosphate of this embodiment includes the following steps: (1) Take 500 mL of deionized water and slowly add 5 g of lithium iron phosphate powder to it and stir to form a uniform suspension.
[0029] (2) Stir continuously for 6 hours at 200 rpm, then filter the solution to remove the lithium iron phosphate material, and then wash twice with 80 mL of deionized water.
[0030] All the above operating environment temperatures and solution temperatures are 25° C. The washed lithium iron phosphate material is dried under vacuum conditions at 120° C. to constant weight (complete drying) to obtain the final product.
[0031] Example 7 The method for processing lithium iron phosphate of this embodiment includes the following steps: (1) Take 500 mL of deionized water and slowly add 5 g of lithium iron phosphate powder to it and stir to form a uniform suspension.
[0032] (2) Stir continuously for 6 hours at 600 rpm, then filter the solution to remove the lithium iron phosphate material, and then wash twice with 80 mL of deionized water.
[0033] All the above operating environment temperatures and solution temperatures are 25° C. The washed lithium iron phosphate material is dried under vacuum conditions at 120° C. to constant weight (complete drying) to obtain the final product.
[0034] Example 8 The method for processing lithium iron phosphate of this embodiment includes the following steps: (1) Take 500 mL of deionized water and slowly add 5 g of lithium iron phosphate powder to it and stir to form a uniform suspension.
[0035] (2) Stir continuously for 6 hours at 1000 rpm, then filter the solution to remove the lithium iron phosphate material, and then wash twice with 80 mL of deionized water.
[0036] All the above operating environment temperatures and solution temperatures are 25° C. The washed lithium iron phosphate material is dried under vacuum conditions at 120° C. to constant weight (complete drying) to obtain the final product.
[0037] Example 9 The method for processing lithium iron phosphate of this embodiment includes the following steps: (1) Take 500 mL of deionized water and slowly add 5 g of lithium iron phosphate powder to it and stir to form a uniform suspension.
[0038] (2) Stir continuously for 8 h at 600 rpm, then filter the solution to remove the lithium iron phosphate material, and then wash twice with 80 mL of deionized water.
[0039] All the above operating environment temperatures and solution temperatures are 25° C. The washed lithium iron phosphate material is dried at 120° C. under vacuum conditions to obtain a constant weight (complete drying) to obtain the final product.
[0040] The lithium iron phosphate treatment method of Example 10-11 is different from that of Example 9 only in the stirring time, and other conditions are the same. In the lithium iron phosphate treatment method of Example 10 and Example 11, the stirring time is 12 hours and 24 hours respectively.
[0041] 2. Comparison The lithium iron phosphate processing method of this comparative example 1 is to take 5 g of lithium iron phosphate powder material consistent with that of Example 1, dry it at 120° C. under vacuum conditions to constant weight (complete drying), and obtain a final product.
[0042] In the methods of Examples 1-11 and Comparative Example 1, a comparison of stirring leaching parameters for the same lithium iron phosphate powder material is shown in Table 1.
[0043] Table 1 Comparison of stirring leaching parameters of Examples 1-8 and Comparative Example 1 3. Experimental Example Application of Lithium Iron Phosphate Materials in Low-Temperature Lithium-Ion Batteries The lithium iron phosphate material obtained in the above embodiments and comparative examples is assembled with a metal lithium sheet and an electrolyte into a CR2032 button battery. The specific preparation process is as follows: based on the total mass of the positive electrode material as 100%, the positive electrode material, the conductive agent SP, the binder (the mass ratio of the positive electrode material, the conductive agent SP, and the binder is 90:5:5) and an appropriate amount of solvent NMP are mixed to form a positive electrode slurry; the positive electrode slurry is then coated on a 12 μm thick aluminum foil, and then dried and sliced into circular electrode sheets with a diameter of 12 mm, and the positive electrode sheets, separators, electrolytes, and metal lithium sheets are assembled into CR2032 button batteries in this order.
[0044] Each lithium iron phosphate battery was subjected to 0.3C constant current charge and discharge test at 25°C, capacity retention rate test at different rates and -40°C discharge capacity retention rate test.
[0045] 0.3C constant current charge and discharge test: Place the battery in a 25℃ constant temperature box, charge it at 0.3C constant current and constant voltage (CC~CV mode) until the voltage is 4.2V, and the cut-off current is 0.05C; after standing for 10 minutes, discharge it at 0.3C constant current to 2.5V, and stand for 10 minutes. Repeat this step three times to get the first cycle charging capacity (the first cycle is the accurate charging capacity, which is directly read by the software).
[0046] Capacity retention rate test at different rates at room temperature: Discharge test at different rates, the test range is 2.5V~4.2V. The specific steps are as follows: Place the battery in a 25℃ constant temperature box, charge at 0.3C constant current and constant voltage (CC~CV mode) to a voltage of 4.2V, and the cut-off current is 0.05C; after standing for 10 minutes, discharge to 2.5V at 0.3, 1, 2, 3, 4, and 10C rates respectively.
[0047] -40℃ discharge capacity retention test: After placing the battery in a 25℃ constant temperature box for 10 minutes, charge it at 0.3C constant current and constant voltage to a voltage of 4.2V, with a cut-off current of 0.05C; then leave it for 5 minutes, discharge it at 0.3C current to 2.5V. Repeat this step three times. After leaving it for 5 minutes, charge it at 0.3C constant current and constant voltage to a voltage of 4.2V, with a cut-off current of 0.05C, and leave it for 5 minutes; then place it in a -40℃ environment for 4 hours, and discharge it at 0.1C current to 1.5V at -40℃.
[0048] 1. First cycle charging capacity test results The test results of the first charge capacity in grams of each embodiment and comparative example are shown in Table 2.
[0049] Table 2 Test results of first cycle charging capacity in grams for each embodiment and comparative example From the experimental results in Table 2, it can be seen that with the increase of washing speed and washing time, after washing for 6 hours, the first cycle charging gram capacity at speeds of 600rpm and 1000rpm is significantly reduced; when the washing speed remains unchanged, with the extension of washing time, the first cycle charging gram capacity gradually decreases and tends to be flat, indicating that the lithium in the lithium iron phosphate material is released during the washing process, and more lithium vacancies are constructed in the lithium iron phosphate material.
[0050] 2. Capacity retention rate test at different rates at room temperature Table 3 Test results of capacity retention rate at different rates of various embodiments and comparative examples at room temperature Electrode Materials 0.3C 1C 2C 3C 4C 10C Example 1 100% 95.23% 92.47% 89.52% 89.05% 82.82% Example 2 100% 95.83% 92.80% 89.89% 89.38% 83.03% Example 3 100% 96.07% 93.15% 91.07% 89.59% 83.29% Example 4 100% 96.21% 93.29% 91.18% 89.72% 83.45% Example 5 100% 96.29% 93.40% 91.29% 89.85% 83.66% Example 6 100% 97.30% 94.06% 91.94% 91.26% 84.12% Example 7 100% 98.65% 95.32% 92.79% 91.94% 85.84% Example 8 100% 98.79% 95.55% 92.95% 92.06% 85.98% Example 9 100% 99.03% 95.96% 93.55% 92.88% 85.83% Example 10 100% 99.86% 96.38% 93.97% 93.39% 86.38% Embodiment 11 100% 99.80% 96.32% 93.89% 93.31% 86.03% Comparative Example 1 100% 96.44% 93.56% 91.47% 89.98% 83.73% From the experimental results in Table 3, it can be seen that with the increase of water washing speed and water washing time, the discharge capacity retention rate at different rates is improved, indicating that water washing improves the kinetics of the material to a certain extent.
[0051] 3. -40℃ discharge capacity retention test The test results of -40°C discharge capacity retention rate of the lithium iron phosphate batteries of the embodiments and comparative examples are shown in Tables 4 and Figure 1 shown.
[0052] Table 4 -40℃ discharge capacity retention test results of various embodiments and comparative examples From Table 4 and Figure 1 It can be seen that under the same water washing time, as the water washing speed increases, the low-temperature discharge capacity retention rate of the battery shows an increasing trend. And after extending the water washing time, the low-temperature discharge capacity retention rate of the battery has also been significantly improved, and the low-temperature kinetic performance has been improved. On the contrary, the battery assembled with lithium iron phosphate material that has not been washed has a lower discharge capacity retention rate at -40°C and poor low-temperature kinetic performance.
[0053] Through the above experiments, it can be seen that the method of the present invention is used to treat lithium iron phosphate raw materials, so that lithium on the surface of the raw materials and in the lattice can be released. After assembling into a lithium iron phosphate battery, the lithium in the positive electrode is significantly reduced, and the lithium vacancies are increased, which effectively improves the low-temperature dynamics of the battery and significantly improves the low-temperature performance of the battery. At the same time, the capacity retention rate of the material at different rates at room temperature is also significantly improved.
Claims
1. A method for treating lithium iron phosphate, characterized in that: The following steps are involved: The lithium iron phosphate is mixed with water, stirred and leached for more than 0.5 hours, and then solid-liquid separation is performed to obtain the lithium iron phosphate material.
2. The method for treating lithium iron phosphate according to claim 1, characterized in that: The stirring leaching time is 0.5~24h.
3. The method for treating lithium iron phosphate according to claim 2, characterized in that: The stirring and leaching time is 6 to 24 hours.
4. The method for treating lithium iron phosphate according to claim 3, characterized in that: The stirring and leaching time is 8 to 24 hours.
5. The method for treating lithium iron phosphate according to claim 1, characterized in that: The stirring speed of the stirring leaching is 200-1000 rpm.
6. The method for treating lithium iron phosphate according to claim 5, characterized in that: The stirring speed of the stirring leaching is 600-1000 rpm.
7. The method for treating lithium iron phosphate according to claim 1, characterized in that: The mixing mass ratio of the lithium iron phosphate and water is 1:100-150.
8. The method for treating lithium iron phosphate according to claim 1, characterized in that: The solid obtained after the solid-liquid separation is washed and vacuum dried to obtain the lithium iron phosphate material; the vacuum drying temperature is 100-150°C.
9. Use of the lithium iron phosphate material obtained by the treatment method according to any one of claims 1 to 8 in a low-temperature lithium-ion battery.
10. The use according to claim 9, characterized in that The low-temperature lithium-ion battery has a 0.1C discharge capacity retention rate of more than 65% at -40°C.
Citation Information
Patent Citations
Preparation method of lithium iron phosphate electrode
CN103400964A